Determine Dispersion Coefficient of 85Rb Atom in the Y–Configuration - Nguyen, Tien Dung (H. : ĐHQGHN, 2019)
In this work, we derive analytical expression for the dispersion coefficient of 85Rb atom for a weak probe laser beam induced by a strong coupling laser beams. Our results show possible ways to control dispersion coefficient by frequency detuning and of the coupling lasers. The results show that a Y-configuration appears two transparent window of the dispersion coefficient for the probe laser beam. The depth and width or position of these windows can be altered by changing the intensity or frequency detuning of the coupling laser fields.